Sleep and Challenging Behaviors in the Context of Intensive Behavioral Intervention for Children with Autism - Abel, Emily A.; Schwichtenberg, A. J.; Brodhead, Matthew T.; Christ, Sharon L. (Journal of autism and developmental disorders, 2018)
This study examined the associations between sleep and challenging behaviors for average and night-to-night fluctuations in sleep, in 39 children with autism spectrum disorder (ASD) receiving intensive behavioral intervention (IBI). Child sleep was recorded (via actigraphy) for five nights in conjunction with clinician-reported observations of challenging behaviors. Results indicated that on average, poor sleep was associated with higher rates of repetitive behavior, negative affect, and a composite of overall challenging behaviors. These findings suggest that average sleep patterns are important within the context of IBI (rather than night-to-night fluctuations). Interventions aimed at improving overall patterns of sleep may have important cascading effects on challenging behaviors and developmental outcomes for children with ASD and their families.